EPISTEMOLOGI PEMIKIRAN ISLAM - A Khudori Soleh, Fathul Lubabin Nuqul (lp2m-uin malang, 2006)
The Development of Islamic knowledge cannot be obtained using western empiricism and rationalism epistemology. Althougth have been considered as the pillar of modern science, substantially, both are different, even they are in compatible with the knowledge in islam. It means that we need to find our own epistemology that goes in accordance with Islam. Related to this, al Farabi and Ibn Rusyd have tried to find the way out although there are still many weaknesses in it.According to Al Farabi, the xsource of the knowledge is active intellect, while ibnu Rusyd said that it comes from reaity and God’s revelation. To get it we have to do many abstractions using demonstrative method. Related to the ratio, Al. farabi used active intellect theory while Ibnu Rusyd preferred the concept of “Inayah”. Using this theory, Al Farabi tried together religion and philosophy into the concept, while Ibn Rusyd let them to be two different things that complete each other.Kata Kunci: Sumber pengetahuan, cara memperoleh pengetahuan, dan hubungan antara wahyu dan rasio